2004
DOI: 10.1152/ajpregu.00715.2003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein malnutrition on IL-6-mediated signaling in the liver and the systemic acute-phase response in rats

Abstract: . Effects of protein malnutrition on IL-6-mediated signaling in the liver and the systemic acute-phase response in rats. Am J Physiol Regul Integr Comp Physiol 287: R801-R808, 2004; 10.1152/ajpregu.00715.2003.-This study examines the effects of malnutrition on IL-6 signaling pathways of rats fed 2% vs. 20% casein diets for 14 days. Effects of malnutrition on the abundance and IL-6-stimulated phosphorylation of signaling proteins in the JAK-STAT and MAP kinase pathways were examined in the liver. Changes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
54
3
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 37 publications
7
54
3
6
Order By: Relevance
“…These conflicting results may indicate that the extent of nutrient restriction might have a significant effect on cytokine production. While the level of restriction imposed in our study was about 40% below the protein and/or energy requirements of the goats, body weight was not affected, indicating that the level of restriction was moderate compared to the acute restriction level imposed by Ling et al (2004). The lack of change in body weight might be due to the reduction of maintenance requirement of energy in PR or ER pregnant goats (Ryan et al 1993).…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…These conflicting results may indicate that the extent of nutrient restriction might have a significant effect on cytokine production. While the level of restriction imposed in our study was about 40% below the protein and/or energy requirements of the goats, body weight was not affected, indicating that the level of restriction was moderate compared to the acute restriction level imposed by Ling et al (2004). The lack of change in body weight might be due to the reduction of maintenance requirement of energy in PR or ER pregnant goats (Ryan et al 1993).…”
Section: Discussioncontrasting
confidence: 51%
“…Nutrient restriction and cytokine production pro-inflammatory cytokines (including TNFa and IL6) compared to rats fed a 20% protein diet (Ling et al 2004). These conflicting results may indicate that the extent of nutrient restriction might have a significant effect on cytokine production.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various cytokines, IL-6 was found to be most closely related to mortality (3,4,6,7) and to be associated with more causes of inflammation than other cytokines and Creactive protein (CRP) (11,12). While an experimental study by Ling et al (13) suggested that protein-energy wasting (PEW) produces changes in inflammationrelated protein characteristics of a low-grade systemic inflammatory response, clinical studies (14 -16) found inflammation, PEW, and cardiovascular morbidity to be interrelated in HD patients, each additionally contributing to the high mortality in HD patients. Therefore, inflammation, as manifested by high levels of IL-6, has been reported as a possible link between PEW and increased cardiovascular morbidity and mortality in chronic HD patients (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…3 Liver total glutathione (GSH) in severe malnourished rat decrease 65% compared to well-nourished rat. 4 This condition is similar to inflammation state. Liver GSH level has an inverse relationship with liver NF-KB activation level, increase IL-1β and TNF-α transcription.…”
mentioning
confidence: 84%